Determination of the optical constants of 2-amino-5-phenyl-1,3,4-thiadiazole by Hartree-Fock and density functional method (B3LYP) - Yakuphanoğlu, Fahrettin; Atalay, Y; Sekerci, M (Elsevier, 2005)
The optical constants (real and imaginary refractive index) and complex dielectric constants of 2-amino-5-phenyl-1,3,4-thiadiazole between 4000 and 400 cm(-1) at 25 degrees C were calculated using the Hartree-Fock and density functional method (B3LYP) and are reported for the first time. The Cauchy parameters obtained from the refractive index spectrum were found to be A = 9.870, B = 2.85 X 10(-5) cm(2) and C = 8.86X 10(-12) cm(4) for experimental results and A = 15.369, B = 3.19 X 10-5 cm(2) and C = 1.49 X 10(-12) cm(4) for HF model and A = 9.871, B = 1.73 X 10(-5) cm(2) and C= 9.24 X 10(-13) cm(4) for B3LYP model, The real and imaginary parts of the complex dielectric constant of the compound were calculated. The real part of the dielectric constant is higher than the imaginary part. The variation of the dielectric constant with photon energy indicates that some interactions between photons and electrons in the film are produced in the investigated energy range. These interactions are observed on the shapes of the real and imaginary parts of the dielectric constant and they cause formation of peaks in dielectric spectra. As a result, the optical constants obtained by using HF and DFT (B3LYP) methods show the best agreement with the experimental data. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin film; refractive index dispersion; complex dielectric constant